Akad Kerja Sama (Syirkah) Perspektif Ekonomi Islam - Hardiati, Neni; Marliani, Arni (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study discusses cooperation (syirkah) in the understanding of Islam both in terms of definition, sources of law, pillars and conditions, types and types and the end of a syirkah. The method used in this research is purely a study of the existing literature. The literature used is sourced from the Qur'an, hadith and opinions from the Imams of the Maliki, Hambali, Hanafi and Shafi'i schools. Other literature that is also used is the opinion of experts in Islamic law.